2017
DOI: 10.1101/lm.044974.117
|View full text |Cite
|
Sign up to set email alerts
|

Synaptically driven phosphorylation of ribosomal protein S6 is differentially regulated at active synapses versus dendrites and cell bodies by MAPK and PI3K/mTOR signaling pathways

Abstract: High-frequency stimulation of the medial perforant path triggers robust phosphorylation of ribosomal protein S6 (rpS6) in activated dendritic domains and granule cell bodies. Here we dissect the signaling pathways responsible for synaptically driven rpS6 phosphorylation in the dentate gyrus using pharmacological agents to inhibit PI3-kinase/mTOR and MAPK/ERK-dependent kinases. Using phospho-specific antibodies for rpS6 at different sites (ser235/236 versus ser240/244), we show that delivery of the PI3-kinase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…The stimulation paradigm was based on the patterns used to induce perforant path LTP, specifically delivery of trains of pulses (8 pulses at 400 Hz, 20 ms duration) at 10 s intervals for 60 or 180 hfrTMS trains. We chose this stimulation paradigm so as to link to our previous studies documenting activation of S6 phosphorylation in the dentate gyrus, which dissected signaling pathways and explored molecular mechanisms (Pirbhoy et al, 2016(Pirbhoy et al, , 2017. It should be noted that different patterns of stimulation are used to induce LTP in hippocampal slices including theta burst stimulation and stimulation with 100 Hz trains.…”
Section: Hz High Frequency Magnetic Stimulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The stimulation paradigm was based on the patterns used to induce perforant path LTP, specifically delivery of trains of pulses (8 pulses at 400 Hz, 20 ms duration) at 10 s intervals for 60 or 180 hfrTMS trains. We chose this stimulation paradigm so as to link to our previous studies documenting activation of S6 phosphorylation in the dentate gyrus, which dissected signaling pathways and explored molecular mechanisms (Pirbhoy et al, 2016(Pirbhoy et al, , 2017. It should be noted that different patterns of stimulation are used to induce LTP in hippocampal slices including theta burst stimulation and stimulation with 100 Hz trains.…”
Section: Hz High Frequency Magnetic Stimulationmentioning
confidence: 99%
“…It should be noted that different patterns of stimulation are used to induce LTP in hippocampal slices including theta burst stimulation and stimulation with 100 Hz trains. However, consequences of these patterns of stimulation on S6 phosphorylation have not been extensively explored, and so we went with the 400 Hz paradigm where data on neurotransmitters and signaling mechanisms have been partially elucidated (Pirbhoy et al, 2017). The most extensive stimulation (180 trains) involved delivery of hfrTMS trains over a 30-min period, which is sufficient to robustly induce S6 phosphorylation in the dentate gyrus (Pirbhoy et al, 2016).…”
Section: Hz High Frequency Magnetic Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…HFS induces localized phosphorylation of ribosomal protein S6, a component of the 40S ribosome detected in polyribosomeenriched fractions from cultured cortical neurons (Krichevsky and Kosik, 2001) and associated with initiating the translation of certain mRNAs (Pirbhoy et al, 2016(Pirbhoy et al, , 2017. Electron microscopy has revealed that the S6 immunoreactivity in dendritic spines is transiently increased at sites were LTP is induced (Nihonmatsu et al, 2015), with a time course similar to that for Camk2a mRNA.…”
Section: Discussionmentioning
confidence: 98%
“…when PV expression first becomes evident during adolescence. This may be achieved as a consequence of activating certain growth factor receptors or potentially via synaptic activity 7,60 in prospective PV-lineages. However, given that Tsc1/2 and other components of the MTOR pathway are expressed in most cell types, there would need to be unique factors coupling MTOR signaling in PV-lineages that are different in SST-lineages.…”
Section: Discussionmentioning
confidence: 99%